2022
DOI: 10.1038/s41398-022-01898-x
|View full text |Cite
|
Sign up to set email alerts
|

Human forebrain organoids reveal connections between valproic acid exposure and autism risk

Abstract: Valproic acid (VPA) exposure as an environmental factor that confers risk of autism spectrum disorder (ASD), its functional mechanisms in the human brain remain unclear since relevant studies are currently restricted to two-dimensional cell cultures and animal models. To identify mechanisms by which VPA contribute to ASD risk in human, here we used human forebrain organoids (hFOs), in vitro derived three-dimensional cell cultures that recapitulate key human brain developmental features. We identified that VPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…A recent study on non-mature human forebrain organoids treated with VPA for 3 days showed primarily alterations in synaptic transmission and ASD-risk genes which correlates with our own findings 53 . However, in our study, we find that these same genes, in addition to other genes encoding chromatin, transcription, and splicing regulators, display differential transcript usage, which may amplify VPA’s effect on gene expression.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study on non-mature human forebrain organoids treated with VPA for 3 days showed primarily alterations in synaptic transmission and ASD-risk genes which correlates with our own findings 53 . However, in our study, we find that these same genes, in addition to other genes encoding chromatin, transcription, and splicing regulators, display differential transcript usage, which may amplify VPA’s effect on gene expression.…”
Section: Discussionsupporting
confidence: 91%
“…The U2F hiPSCs was obtained from the Cellapy Technology (Beijing, China), and the ACS-1011 was obtained from the American type culture collection (ATCC). Pluripotency and karyotype of U2F hiPSCs were con rmed by immuno uorescence and karyotype analysis as shown in our previous studies 46, 47 . The hiPSCs were cultured in Matrigel (Corning, 354277)-coated plate and supplemented with the mTeSR Plus medium (STEMCELL Technologies, 05825) and 1% penicillin/streptomycin (Gibco, 10378016).…”
Section: Cell Culturementioning
confidence: 53%
“…From day 43, organoids were cultured in the Forebrain Organoid Maintenance Medium. hFOs were characterized using immunostaining as described in our previous studies 46, 47 .…”
Section: Generation Of Hfosmentioning
confidence: 99%
“…One recent study has found that VPA exposure in human forebrain organoids caused altered many ASD risk gene expression ( Meng et al, 2022 ). Consistent with this, organoid RNA sequencing displayed that VPA treatment changed the levels of ASD risk genes, which overlapped with aberrant genes in ASD brains and patient-derived brain organoids.…”
Section: Discussionmentioning
confidence: 99%